Cultivation of Chlorella vulgaris using sequential-flow bubble column photobioreactor: A stress-inducing strategy for lipid accumulation and carbon dioxide fixation. Issue 41 (October 2020) - Dasan, Yaleeni Kanna; Lam, Man Kee; Yusup, Suzana; Lim, Jun Wei; Show, Pau Loke; Tan, Inn Shi; Lee, Keat Teong
Graphical abstract: Highlights: Sequential flow photobioreactor system was used to maximize CO2 fixation efficiency. The C. vulgaris growth was promoted by optimizing the cultivation parameters. CO2 removal efficiency in a sequential-flow system increased by 3.78-fold. Highest lipid content was attained for microalgae grown in the spent medium. Abstract: Biological CO2 fixation by microalgae coupled with value-added product creation appears to be a sustainable approach in microalgae-based industry. However, the major constraint of this process is the low solubility of CO2 in water which limits CO2 fixation ability by the microalgae. Therefore, the current work aimed to improve the CO2 fixation efficiency of Chlorella vulgaris through the introduction of sequential-flow bubble column photobioreactor system. The influence of various cultivation parameters towards the growth, carbon fixation efficiency, lipid accumulation, and fatty acid profile of C. vulgaris were explored. Experimental results showed that microalgae cultivated under optimized conditions attained the highest biomass productivity (0.83−0.86 g/L/day) as compared to the control conditions. Meanwhile, the highest lipid content (50.4 % for SFB-PBR1) was recorded when the microalgae were cultivated in the spent medium. In addition, the CO2 fixation efficiency by microalgae in the sequential-flow photobioreactor system under the optimized condition was 3.78-fold higher than a single column mode (control). In short, the present work had demonstrated that cultivation conditions and photobioreactors configuration were equally important for an effective carbon capture process via microalgae cultivation.